2021
DOI: 10.1111/1475-6773.13652
|View full text |Cite
|
Sign up to set email alerts
|

Operational Modeling with Health Economics to Support Decision Making for COPD Patients

Abstract: Objective To assess the impact of interventions for improving the management of chronic obstructive pulmonary disease (COPD), specifically increased use of pulmonary rehabilitation (PR) on patient outcomes and cost‐benefit analysis. Data Sources We used the national Hospital Episode Statistics (HES) datasets in England, local data and experts from the hospital setting, National Prices and National Tariffs, reports and the literature around the effectiveness of PR programs. Study Design The COPD pathway was mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Compared to usual care, pulmonary rehabilitation leads to substantial improvements in dyspnea, exercise capacity, and health status [ 25 ]. Furthermore, when provided following hospitalizations for COPD exacerbation, it has pronounced benefit in reducing subsequent hospitalization and mortality risk [ 55 ], and referral leads to projected favorable benefit–cost analyses, both from a systematic review [ 56 ], and across different health care settings in the United Kingdom [ 57 ].…”
Section: Telemedicinementioning
confidence: 99%
“…Compared to usual care, pulmonary rehabilitation leads to substantial improvements in dyspnea, exercise capacity, and health status [ 25 ]. Furthermore, when provided following hospitalizations for COPD exacerbation, it has pronounced benefit in reducing subsequent hospitalization and mortality risk [ 55 ], and referral leads to projected favorable benefit–cost analyses, both from a systematic review [ 56 ], and across different health care settings in the United Kingdom [ 57 ].…”
Section: Telemedicinementioning
confidence: 99%
“…In the last 2 decades there has been an explosive increase in the number of DES publications and a claimed diffusion of DES into healthcare 8 . It has been observed that the applications of DES are largely confined to specific health care units, with modelling of emergency departments the most popular setting 9,10 and many applications seeking to improve time‐ and efficiency‐related metrics 9,11 and cost‐effectiveness 12 . A recent systematic review found an increasing trend towards using DES in healthcare to address issues at an operational level, yet less than 10% of DES applications presented actual implementations following the modelling stage 9 .…”
Section: Introductionmentioning
confidence: 99%
“…8 It has been observed that the applications of DES are largely confined to specific health care units, with modelling of emergency departments the most popular setting 9,10 and many applications seeking to improve time-and efficiency-related metrics 9,11 and cost-effectiveness. 12 A recent systematic review found an increasing trend towards using DES in healthcare to address issues at an operational level, yet less than 10% of DES applications presented actual implementations following the modelling stage. 9 The review advocates that future research should focus on the implementation of models, overcoming critical barriers such as security and privacy and obtaining acceptance for change from healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…33 Although it is reassuring that these prior results are consistent with our present findings, our study has several important differences. In addition to including routinely reported costs of PR, rehospitalization, and ED use, [17][18][19]34 we included the costs of SNF days, which to date have been reported infrequently (Table 1). In addition, we included data from multiple large data sources using clinical evidence, 10,11 in contrast to most prior studies that used single-center clinical trial data.…”
Section: Discussionmentioning
confidence: 99%